ChemInform Abstract: Electrical and Thermal Transport Properties of AgIn5Te8. Issue 30 (4th July 2013) - Pei, Yan‐Ling; Zhang, Chaolei; Li, Jing; Sui, Jiehe
Abstract AgIn5Te8 is synthesized by reactive melting of a stoichiometric mixture of Ag, In, and Te (C‐coated evacuated fused silica tube, 1073 K, 6 h).